LOCAL POLITICAL DYNAMICS IN THE IMPLEMENTATION OF THE PROGRAM FOR INNOVATION IN REGIONAL DEVELOPMENT AND EMPOWERMENT (PIPPK) IN BANDUNG CITY - Talia, Hafshah; Ningrum, Sinta; Sukarno, Dedi (JWP (Jurnal Wacana Politik), 2025)
Local Political Dynamics in the Implementation of the Program for Innovation in Regional Development and Empowerment (PIPPK) in Bandung City examines how local political dynamics influence the implementation of the PIPPK policy. This study focuses on analyzing the interactions among stakeholders, including the Regional Governance Section of Bandung City, subdistrict heads, community leaders, and local political actors, as well as the challenges arising from these dynamics. The research qualitative primary data from in-depth interviews and field observations with secondary data from media documentation and previous studies. The findings indicate that local political dynamics affect decision-making processes, resource allocation, and the effectiveness of PIPPK implementation. Consistent support from the city government and synergy among stakeholders are key to the successful implementation of this policy. The study also emphasizes the importance of strategic approaches to enhancing transparency, decentralizing authority, and actively involving the community to address existing challenges. The findings of this study reveal that the interactions between local government, subdistrict heads, community leaders, and local political actors in the implementation of PIPPK in Bandung City are often shaped by political interests and power dynamics. Local government officials and subdistrict heads coordinate the program, while community leaders help facilitate its implementation. However, political actors sometimes influence decision-making, prioritizing political gains over program objectives. The main challenges include political fragmentation, limited community involvement, and the dominance of patronage networks, all of which can hinder effective collaboration and the achievement of the program’s goals in community empowerment and regional development..